Sejarah dan Perkembangan Muhammadiyah di Kabupaten Pasaman Barat - Abdul Hakim; Erniwati Erniwati (PAMA Aksara, 2019)
Muhammadiyah has emerged and developed in West Sumatra since 1925. The development of Muhammadiyah in this region is much more rapid than the place of birth of Yogyakarta, so that West Sumatra is called as a place for Muhammadiyah to be raised. In the West Pasaman district Muhammadiyah has been in since 1928, by forming the Muhammadiyah Talu group. It was this group that later became the forerunner to the establishment of the West Pasaman Regional Muhammadiyah Leader. Writing the history and development of West Pasaman Muhammadiyah uses a historical method consisting of heuristics (collecting resources), criticizing the sources to find the authenticity and credibility of the data, interpretation (understanding of the text) and ending with historiography (writing history). The results of this study indicate that the West Pasaman Muhammadiyah had existed long before the formation of the West Pasaman government. In its development, West Pasaman Muhammadiyah faced the dynamics of ethnic diversity as well as customs and culture in the area. Through propaganda and charity efforts Muhammadiyah began to be accepted in areas that initially rejected this association.